2022
DOI: 10.4103/jomfp.jomfp_138_21
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of inflammatory, angiogenic, and fibrous components of reactive oral lesions with an insight into the pathogenesis

Abstract: Background: Reactive oral lesions pose diagnostic difficulties as they mimic each other clinically. A definitive diagnosis is made based on the histopathological presentation of this group of lesion. Stromal microenvironment is the key to the sequence of the stages of these lesions. Stringent quantification of each component of the stroma is important to understand the pathogenesis. The aim is to evaluate inflammation, angiogenesis, and fibrosis in the reactive group of lesions through quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Cropped ROIs are saved as .tiff files and subsequently targeted by the quantification algorithm, which has been computed by using the integrated density (ID) as the sum of all pixels within a region; indeed, a plethora of evidence has shown that ID is a reliable measure in this field [14,15].…”
Section: Rois Croppingmentioning
confidence: 99%
“…Cropped ROIs are saved as .tiff files and subsequently targeted by the quantification algorithm, which has been computed by using the integrated density (ID) as the sum of all pixels within a region; indeed, a plethora of evidence has shown that ID is a reliable measure in this field [14,15].…”
Section: Rois Croppingmentioning
confidence: 99%
“…Fibroepithelial hyperplasias are a diagnostic challenge. It may mi mic various pathologic processes, rarely even malignant lesions (99,100). Excision of the lesion is the choice of treatment, and there is a need for histopathological analysis to confirm the clini cal diagnosis (100).…”
Section: Diagnosismentioning
confidence: 99%
“…It may mi mic various pathologic processes, rarely even malignant lesions (99,100). Excision of the lesion is the choice of treatment, and there is a need for histopathological analysis to confirm the clini cal diagnosis (100). Histology shows fibroepithelial hyperplasia often with diffuse and mild lymphoplasmacytic inflammatory in filtration.…”
Section: Diagnosismentioning
confidence: 99%